Sistema de auxílio a navegação em ambientes internos para pessoas com deficiência visual usando visão estereoscópica - Chiqueto, Thiago Sousa (2016)
Considering the high rate of people with some kind of visual impairment, and, moreover, that most of these people have a low income, this work is proposed to create a navigation system in indoors environment through equipment low cost. Using Python as programming language, together with the OpenCV library, the main objective of this research is to extract a disparity map and perform testing on different platforms with application filters images generated by the stereoscopic vision camera Minoru3D for mapping indoor environments, informing the user the free way for locomotion.